Effective Benefit Program - Suhartini Suhartini (Jurnal Aplikasi Bisnis, 2017)
Benefit Program (BP) is the financial compensation provided indirectly to the employees, including 3 (three) categories, namely: income protection Programmes, reimbursed time off and empl(yee services and perquisites. BP offered a firm reflects the specific decisions made by managers. For companies, BP is offered to strengthen the emergence of a sense of caring and belonging as a family on the employees them selves. For employees, BP is provided by the company can help meet their physical and economic needs, and will ultimately spur performance. Therefore, BP can also be linked to individual performance and company performance. BP is a major cost for employers and as a key element of compensation that will affect the satirfaction of the employee. Today many companies devlop creative BP, leaving BP with the traditional concept of one-size-fits-all and offers the flexibility for employees to choose a BP that can meet the unique needs of each employee